Analisis Pengaruh Faktor Fundamental Terhadap Return Saham - Sheilla Nurlailly Insani; Nancy Nurinasari; Laili Ayu Sa’diah; Denny Oktavina Radianto (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2019)
This study aims to examine: (1) the effect of EPS on stock prices, (2) the effect of ROE on stock prices, (3) the effect of DER on stock prices, (4) the effect of ROA on stock prices, (5) simultaneous influence of EPS, ROE, DER, and ROA on stock prices. This research use stock returns as the dependent variable and EPS, ROE, DER, and ROA as independent variables. This study use secondary data from the annual financial statements of the property and real estate industry groups listed on the Indonesia Stock Exchange from 2013 to 2017 with using the judgment sampling method to produce 7 companies that meet the sample criteria. This study uses an associative type method with a quantitative approach. The analysis technique used is descriptive statistical analysis, classic assumption test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, and hypothesis testing. This research was conducted by retrieving data through the website www.idx.co.id which was processed based on research needs using the SPSS version 23. The results showed that the EPS, ROE, DER, and ROA ratios did not significantly influence stock returns of property and real estate listed on the Indonesia Stock Exchange.